Assessment of future climate change impact on water balance components in Central Rift Valley Lakes Basin, Ethiopia. Issue 1 (21st December 2022) - Balcha, Sisay Kebede; Awass, Adane Abebe; Hulluka, Taye Alemayehu; Bantider, Amare; Ayele, Gebiaw T.
Abstract: This study aims to assess the impact of climate change on the water balance component of the Katar and Meki watersheds of the Central Rift Valley Lakes Basin, Ethiopia. The semi-distributed soil and water assessment tool hydrological model and multiple regional climate model outputs were used to assess climate change impacts on water balance components and stream flow. Future climate scenarios were developed under a representative concentration pathway (RCP 4.5 and 8.5) for the 2040s (2021–2050) and 2070s (2051–2080). The study found that future annual and seasonal rainfall will show increasing and decreasing trends but that they are statistically insignificant. Furthermore, future temperatures show a significant increase in the subbasins. For the applied scenarios, an increasing and decreasing trend of future rainfall and increased temperatures would decrease the water yield by 4.9–15.3% at the Katar subbasin and 6.7–7.4% at the Meki subbasin. Furthermore, annual water yields will increase in the range of 0.38–57.1% and 6.57–49.9% for the Katar and Meki subbasins, respectively. The findings of this study will help basin planners, policymakers, and water resource managers develop appropriate adaptation strategies to mitigate the negative effects of climate change in the rift-bound lake system. HIGHLIGHTS: The baseline and future rainfall show increasing and decreasing trends but are statistically not significant. The selected bias correction methods were significantly improved and add value to the RCMs outputs. Changes in the climate variables reduce the annual water yield and stream flow under all climate scenarios except RCP 4.5 by 2070. Graphical Abstract